100 anos da revolução russa: Ensinamentos da atuação dos anarquistas - De Moraes, Isaías Albertin [UNESP]; Da Costa Vieira, Fernando Antonio (Universidade do Estado de Santa Catarina, 2017)
This article seeks to present, in the 100 years celebration of the Russian Revolution, a historical analysis of anarchist participation in the pre-revolution process and during the years of War Communism. In a second moment, the research sought to describe the main anarchist movement during the Russian Revolution, the activity of Nestor Ivanovitch Makhno and his Black Army in the Ukraine.
100th anniversary of Russian revolution: Lessons of anarchists’s action
Keywords: Anarchism; Makhnovist movement; Russian revolution 1917; Social movements